Relationship between models of care and key rehabilitation milestones following unilateral transtibial amputation: a national cross-sectional study. Issue 4 (December 2019) - Hebenton, J.; Scott, H.; Seenan, C.; Davie-Smith, F.
Abstract: Objectives: To identify different models of care (MOC) post transtibial amputation (TTA) and relate these to achievement of rehabilitation milestones. Design: Retrospective analysis of rehabilitation milestone data and a survey of MOC in 10 vascular centres. Setting: NHS Scotland vascular centres. Participants: All unilateral TTA between January 2011 and December 2014 ( n  = 643). Main outcome measures: Time (in days) to achieve the following rehabilitation milestones: compression therapy, early walking aid, casting for a prosthetic limb, prosthetic delivery, inpatient discharge and final discharge from rehabilitation. MOC were scored according to seven key aspects of service provision. Results: The mean age of the cohort was 67 [standard deviation (SD) 13] years, 76% were male and 63% had peripheral arterial disease and diabetes. The median number of days to achieve rehabilitation milestones varied between centres {compression therapy six [interquartile range (IQR) 0–12], early walking aid 14 (IQR 10–27), prosthetic casting 39 (IQR 27–71), prosthetic delivery 53 (IQR 36–87), inpatient discharge 53 (IQR 29–85) and final discharge from rehabilitation 141 (IQR 92–209)}. Only two centres included all seven key aspects of service provision within their MOC. Vascular centres that achieved the optimal MOC achieved the rehabilitation milestones more quickly than other vascular centres. Conclusions: A positive association was found between optimal MOC and early achievement of rehabilitation milestones post TTA. Key aspects of service provision associated with a quicker time to achieve rehabilitation milestones included: use of a postoperative rigid dressing, specialist physiotherapy input in the early postoperative period, daily inpatient gym sessions and inpatient prosthetic provision. To the authors' knowledge, this is the first study to document MOC following TTA and to relate these to the achievement of rehabilitation milestones.